Enzyme replacement therapy for the treatment of late onset Pompe disease: A systematic review and network meta-analysis - Mark Corbett; Chinyereugo Umemneku-Chikere; Sarah Nevitt; Nyanar Jasmine Deng; Matthew Walton; Helen Fulbright; Chong Yew Tan; Robin Lachmann; Rachel Churchill; Robert Hodgson (Orphanet Journal of Rare Diseases)
Abstract Background Late-onset Pompe disease (LOPD) is a rare inherited genetic condition caused by deficiency of acid α-glucosidase (GAA) and accumulation of lysosomal glycogen. LOPD causes progressive muscle dysfunction and damage, leading to significant morbidity and early mortality. Enzyme replacement therapy (ERT) is the primary treatment for Pompe disease. Methods A systematic review and network meta-analysis of published evidence on the clinical effectiveness of ERT and best supportive care (BSC) was undertaken to establish the relative effectiveness of ERT compared to BSC (in the absence of ERT). Bibliographic databases were searched to identify randomised controlled trials (RCTs) or any other prospective ERT studies in patients with Pompe disease. Network meta-analyses (NMA) of RCTs were undertaken to estimate indirect treatment effects for forced vital capacity (FVC) % predicted and the 6-minute walk test (6MWD). A narrative synthesis was employed to summarise other studies. Results A total of 38 studies were included in the review. They comprised three RCTs, three RCT extension studies, seven registry studies and 25 single-group prospective studies. The results of two RCTs were judged to have a high risk of bias. In the NMA, after approximately one year, ERT-naïve patients showed significant 6MWD improvements vs. placebo: ~25 m with alglucosidase alfa and ~ 54 m with avalglucosidase alfa. No significant differences were found for FVC % predicted or comparisons with cipaglucosidase alfa, although very few ERT-naïve patients taking cipaglucosidase alfa were available for the analyses. Intra-ERT comparisons showed a significant 6MWD advantage for avalglucosidase alfa. However, a sensitivity analysis adjusting for skewed data revealed no significant differences. Long-term ERT effectiveness was assessed in single-group studies, showing initial gains maintained for 1–3 years, followed by gradual 10–15-year declines in 6MWD and FVC % predicted. However, small sample sizes and missing data introduce uncertainty. Conclusions Our NMA results showed that ERTs lead to modest improvements in 6MWD after 1 year compared to placebo in ERT-naive populations. However, there is limited evidence supporting meaningful differences in outcomes between ERTs. There is a lack of longer-term follow-up data supporting the effectiveness of ERTs compared to each other and to best supportive care.